2019
DOI: 10.1136/annrheumdis-2018-214323
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of STAT1 and HLA-DRB1 is associated with type-I interferon-dependent HLA-DRB1 expression in lupus CD8+ T cells

Abstract: ObjectiveWe examined genome-wide DNA methylation changes in CD8+ T cells from patients with lupus and controls and investigated the functional relevance of some of these changes in lupus.MethodsGenome-wide DNA methylation of lupus and age, sex and ethnicity-matched control CD8+ T cells was measured using the Infinium MethylationEPIC arrays. Measurement of relevant cell subsets was performed via flow cytometry. Gene expression was quantified by qPCR. Inhibiting STAT1 and CIITA was performed using fludarabine an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Comparing Ostrava and Prague, the most hypomethylated DML was found to be CpG locus cg10123377. This CpG locus was also found in the study of patients with systematic lupus erythematosus in CD8T+ cells [38]. Two of the hypermethylated loci (cg11478607 and cg26946806) located in Island and S Shore, respectively, are annotated to the GSTT1-encoding xenobiotic metabolizing enzyme, which plays an important role in human carcinogenesis [39] and impacts the markers of genotoxicity [40].…”
Section: Discussionmentioning
confidence: 72%
“…Comparing Ostrava and Prague, the most hypomethylated DML was found to be CpG locus cg10123377. This CpG locus was also found in the study of patients with systematic lupus erythematosus in CD8T+ cells [38]. Two of the hypermethylated loci (cg11478607 and cg26946806) located in Island and S Shore, respectively, are annotated to the GSTT1-encoding xenobiotic metabolizing enzyme, which plays an important role in human carcinogenesis [39] and impacts the markers of genotoxicity [40].…”
Section: Discussionmentioning
confidence: 72%
“…Consistently, the rs9267649 protective variant was associated with increased DNA methylation and lower HLA-DRB1 expression in multiple sclerosis [119]. Furthermore, hypomethylation of HLA-DRB1 loci also induces HLA-DRB1 expression in systemic lupus erythematosus CD8+ T cells [120]. The HLA-DRB1 methylation status is likely to be relevant to RA, also.…”
Section: Significance Of Hla-drb1 Methylation Statusmentioning
confidence: 75%
“…Interestingly, when |Db| ≥ 0.1 (simultaneously p < 0.01), 4 of the 28 DMGs-HLA-DPB2, HLA-DRB1, PPP2R5C, and LTF, which all mapped from more than one CpG site-are all associated with autoimmunity. Moreover, HLA-DRB1 has been reported to be related to the DNA methylation of multiple autoimmune diseases including Crohn's disease, multiple sclerosis, SLE, and TID (23)(24)(25)(26). A recent study has revealed that the only one DMG with mixed methylation, fibrinogen-like protein 2 (FGFR2), is a mast cell mediator with potential relevance in CSU (27).…”
Section: Discussionmentioning
confidence: 99%